Knowledge, attitude, and practice regarding osteoporosis among allied health sciences students in a public university in Malaysia - Ramli, Nabilah; A. Rahman, Nor Azlina; Haque, Mainul (Erciyes University Faculty of Medicine, 2018)
Objective: Osteoporosis is usually asymptomatic until the first fracture occurs. The tendency of developing osteoporosis is higher in postmenopausal women. The purpose of the present study was to analyze the knowledge, attitude and practice (KAP) regarding osteoporosis among Allied Health Sciences students in a public university in Malaysia, its associated sociodemographic factors, and association between the KAP. Materials and Methods: This was a cross-sectional study. The participants who were selected using convenience sampling were given a questionnaire that comprised four sections on sociodemographic and KAP regarding osteoporosis. Descriptive statistics, independent t-test, and correlation test were used accordingly to analyze data using SPSS version 20. Results: The total KAP scores were 39.62 (SD=2.87), 35.82 (SD=4.72), and 20.34 (SD=2.86), respectively. There was no significant association between KAP regarding osteoporosis with sexes (p=0.063, p=0.723, and p=0.162, respectively) of the participants, neither between knowledge and attitude with age (p=0.784 and p=0.366, respectively), or year of study (p=0.833 and p=0.468, respectively) of the participants. However, there was a minimal significant negative correlation between practice with age and year of study of the participants (r=-0.230, p=0.017 and r=-0.238, p=0.014, respectively). Finally, there was also a significant fair positive correlation between attitude and practice regarding osteoporosis (r=0.339, p<0.001). Conclusion: The participants in the present study had moderate/fair level of knowledge and attitude but poor practice regarding osteoporosis. Only age and year of study were found to be significantly negatively associated with practice, in addition to the fair positive correlation between attitude and practice.